Directional Audio Coding with stereo microphone input - Ahonen, Jukka; Pulkki, Ville; Kuech, Fabian; Del Galdo, Giovanni; Kallinger, Markus; Schultz-Amling, Richard (126th Audio Engineering Society Convention 2009, 2009)
The use of stereo microphone configuration as input to teleconference application of Directional Audio Coding (DirAC) is presented. DirAC is a method for spatial sound processing, in which the direction of the arrival of sound and diffuseness are analyzed, and used for different purposes in reproduction. So far, omnidirectional microphones arranged in an array have been used to generate input signals for one-and two-dimensional sound field analysis in DirAC teleconferencing. In this study, the possibility to use domestic stereo microphones with DirAC analysis is investigated. Different methods to derive omnidirectional and dipole signals from stereo microphones for directional analysis are presented, and their applicability is discussed.
CRIS-Team Scopus Importer:2025-11-10